1986
DOI: 10.1111/j.1365-2125.1986.tb05191.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ranitidine in critically ill patients.

Abstract: 1 The plasma pharmacokinetics of ranitidine (50 mg i.v.) have been studied in 17 critically ill patients in an intensive care unit. Measurements of gastric aspirate pH were also made in 16 of these patients. Ranitidine therapy was part of the patients' normal drug regimen. 2 Ranitidine plasma concentration was measured by high performance liquid chromatography and appropriate polyexponential equations were fitted to concentration-time data to enable calculation of relevant pharmacokinetic parameters. Values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The pharmacokinetic model developed in the present study revealed considerable IIV in the CL and V of ranitidine in critically ill children. This variability concurs with previously reported data obtained in critically ill adults and children in the paediatric intensive care unit . The estimated IIV (CV%) in the BASE model was 83.7 and 84.0% for CL and V , respectively (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…The pharmacokinetic model developed in the present study revealed considerable IIV in the CL and V of ranitidine in critically ill children. This variability concurs with previously reported data obtained in critically ill adults and children in the paediatric intensive care unit . The estimated IIV (CV%) in the BASE model was 83.7 and 84.0% for CL and V , respectively (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…Intravenous ranitidine is widely used as a prophylactic agent for stress ulcer–related bleeding in patients in an ICU 10 . Different intravenous regimens, repeated bolus injections, and primed continuous infusions have been used in patients in ICUs and tested in healthy volunteers 11 , 12 , 13 , 14 , 15 , 16 , 17 . However, the clinical responses and the conclusions drawn from these trials have often been contradictory 7 , 18 .…”
mentioning
confidence: 99%
“…Another study reported that ranitidine CL in critically ill children increased during the study period possibly due to concomitant administration of CYP inducers resulting in a reduced efficacy when recommended doses were administered [172]. All studies report that the ranitidine PK is highly variable in both critically ill adults and children and thus it is not possible to reliably compare the alterations [170174]. …”
Section: Pharmacokinetic Studies In Critically Ill Childrenmentioning
confidence: 99%